2022
DOI: 10.3390/horticulturae8100967
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Data Revealed Metabolite Changes during Endocarp Lignification in Kernel-Using Apricot

Abstract: To understand the metabolite dynamics and genetic regulatory mechanism of apricot shell, a typical endocarp, before and after lignification are unknown, we investigated the metabolite differences of the endocarp of ‘Youyi,’ a popular kernel-using apricot cultivar, using ultra-performance liquid chromatography tandem mass spectrometry strategy. The endocarp thickness increased rapidly from 8 to 37 days after flowering (DAF) and lignin deposition began at 37 DAF. In total, 626 non-volatile metabolites were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…We found locus qtnSTH_2.2 on Chr2 in the region of 7.59–9.45 Mb, which is related to multiple tandem genes associated with lignin synthesis and regulation, such as phenylalanine ammonia-lyase ( Pa02g07108.1 and Pa02g07109.1 ), tyramine N-feruloyltransferase ( Pa02g07115.1 and Pa02g07116.1 ), three caffeic acid 3-O-methyltransferase genes ( Pa02g07215.1 , Pa02g07216.1 , and Pa02g07217.1 ), and seven 3-hydroxyisobutyryl-CoA hydrolase genes. This result is consistent with the differences in expression at the transcriptional and metabolic levels ( Zhang et al., 2022a ). We still need to dissect trait-rich QTL regions and narrow QTL regions to reduce the number of candidate genes, and the development of marker-assisted selection tools with high accuracy and efficiency is necessary for kernel-using apricot breeding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found locus qtnSTH_2.2 on Chr2 in the region of 7.59–9.45 Mb, which is related to multiple tandem genes associated with lignin synthesis and regulation, such as phenylalanine ammonia-lyase ( Pa02g07108.1 and Pa02g07109.1 ), tyramine N-feruloyltransferase ( Pa02g07115.1 and Pa02g07116.1 ), three caffeic acid 3-O-methyltransferase genes ( Pa02g07215.1 , Pa02g07216.1 , and Pa02g07217.1 ), and seven 3-hydroxyisobutyryl-CoA hydrolase genes. This result is consistent with the differences in expression at the transcriptional and metabolic levels ( Zhang et al., 2022a ). We still need to dissect trait-rich QTL regions and narrow QTL regions to reduce the number of candidate genes, and the development of marker-assisted selection tools with high accuracy and efficiency is necessary for kernel-using apricot breeding.…”
Section: Discussionsupporting
confidence: 91%
“…Apricots are widely cultivated in the Northern Hemisphere and can be classified as fresh-using, kernel-using, and ornamental apricots according to their utilization purpose. Because of their hardiness and cold and drought tolerance ( Zhang et al., 2022a ), kernel-using apricots are an economically important fruit tree species in arid areas. In China, the area and annual output of kernel-using apricots are approximately 957,000 hm² and 300,000 t, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ES treatments increased the expression of l -phenylalanine (the initial substrate for phenylpropanoid biosynthesis) and 4-hydroxycinnamate in blueberry fruits under Cd toxicity (Figure B), which may be the result of ESs promoting the production of phenolic metabolites to alleviate the oxidative damage of Cd toxicity to blueberry fruits . Coniferin, a downstream product of cinnamic acid, plays an important role in pericarp lignification and response to abiotic stress . Our results showed that ES treatments significantly elevated coniferin levels in blueberry fruits under Cd toxicity.…”
Section: Discussionmentioning
confidence: 50%
“…53 Coniferin, a downstream product of cinnamic acid, plays an important role in pericarp lignification and response to abiotic stress. 54 Our results showed that ES treatments significantly elevated coniferin levels in blueberry fruits under Cd toxicity. Besides, ESs also significantly up-regulated the expression of Spd (Figure 4B), which, as an important amino acid metabolite involved in the phenylpropanoid biosynthesis, is closely related to antioxidant and anti-inflammatory bioactivities of fruits.…”
Section: Discussionmentioning
confidence: 50%
“…Extensive research has been conducted on lignin biosynthesis pathways, and the enzymes involved have been extensively described [17,18]. Cytochrome P450 oxidoreductases, including (C4H), (C3H), and (F5H), are responsible for aromatic ring hydroxylation [15], while other monolignol biosynthetic enzymes, such as (PAL), (4CL), (HCT), (CSE), (CcOAMT), (CCR), (COMT), and (CAD), are present in the cytoplasm [19].…”
Section: Molecular Mechanism Of Lac Genes Involved In Fruit Endocarp ...mentioning
confidence: 99%